2020
DOI: 10.1016/j.lungcan.2020.08.011
|View full text |Cite
|
Sign up to set email alerts
|

The Dutch Lung Cancer Audit: Nationwide quality of care evaluation of lung cancer patients

Abstract: This study describes the initiation of the Dutch Lung Cancer Audit for Lung Oncology (DLCA-L) and reports the first results of three years of clinical auditing. Methods: The initiation, dataset, and data quality of the DLCA-L are described. For the analyses, all patients registered from 2017 to 2019 were included. Descriptive statistics were used to assess the first outcomes of the DLCA-L, including results from quality indicators, patient-and tumor characteristics, and the real-world use of immunotherapy. Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 18 publications
0
27
1
Order By: Relevance
“…In comparison, results from the Dutch Lung Cancer Audit reported that the use of immunotherapy in stage III NSCLC was only 13% in 2018, but increased to 25% in 2019. 18 This finding could be explained by the fact that only a limited number of Dutch institutions were initially allowed to prescribe durvalumab. 18 Most centers participating in our study had early access to durvalumab for their patients, but durvalumab was recorded as being unavailable in 9% of eligible patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In comparison, results from the Dutch Lung Cancer Audit reported that the use of immunotherapy in stage III NSCLC was only 13% in 2018, but increased to 25% in 2019. 18 This finding could be explained by the fact that only a limited number of Dutch institutions were initially allowed to prescribe durvalumab. 18 Most centers participating in our study had early access to durvalumab for their patients, but durvalumab was recorded as being unavailable in 9% of eligible patients.…”
Section: Discussionmentioning
confidence: 99%
“… 18 This finding could be explained by the fact that only a limited number of Dutch institutions were initially allowed to prescribe durvalumab. 18 Most centers participating in our study had early access to durvalumab for their patients, but durvalumab was recorded as being unavailable in 9% of eligible patients. Our real-world data are consistent with other reports indicating only between 34% and 73% of patients receive durvalumab after CCRT, with similar reasons being cited for noncompliance.…”
Section: Discussionmentioning
confidence: 99%
“…7 Tumour specific oncology QIs are also reported in retrospective annual patterns of care audits by a number of countries. [8][9][10][11] An updated framework for modern cancer care was recently proposed by Chiew et al to incorporate 12 areas for quality of care expanding upon the Donabedian model of structural (timeliness, access and healthcare delivery systems) process (appropriateness of treatment, technical, multidisciplinary discussion/coordination of care, patient reported experiences (PRE) and satisfaction) and outcome domains (disease-specific survival, patient reported outcomes (PRO), safety and adverse events, with all areas also needing to include value and innovation/improvement. 12 Oncology QIs are commonly developed and derived via an established methodology of evidence-based literature search, modified Delphi process and expert consensus/concordance voting.…”
Section: Oncology Qismentioning
confidence: 99%
“…Stage III (locally advanced) non-small cell lung cancer (NSCLC) represents approximately 20% of all new lung cancer diagnoses [ 1 , 2 ]. Many patients are elderly with significant co-morbidities, and multidisciplinary tumor board review is recommended to determine the best treatment strategy [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%